2019
DOI: 10.1002/ente.201801147
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Molybdenum Disulfide/Carbon Nanocomposites in Polyacrylic Acid Hydrogel as Anode for Lithium‐Ion Batteries

Abstract: Molybdenum disulfide (MoS2)/carbon nanocomposites are grown in a polyacrylic acid (PAA) hydrogel system via a facile hydrothermal process and carbonization of PAA by heat treatment under an argon atmosphere. The content of the MoS2 electrode material can be controlled effectively by adjusting the immersing time of the MoS2 precursor with PAA hydrogel. The MoS2/carbon nanocomposites containing MoS2 nanosheets are uniformly embedded in a 3D interconnected network carbon matrix. The unique network structure as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…Additionally,t he discharge platformso ft he NCM-NC and M-NF electrodes shift to lower voltages at high current density,w hich implies that more electrons are congested on the surfaceo ft he electrode (FigureS6b,c in the Supporting Information). [36] The specific capacity of the hollow NiÀ Co skeletons essentially remained stable during the first 200 cycles. Figure 6c displays the cycling performance of NCM-NC,M -NF,a nd NiÀCo skeleton electrodes at ac urrent density of 0.2 Ag À1 over the voltage range of 0.01-3.0 V. The M-NF electrode exhibits as lowly increasing trend during the first 155 cycles because the M-NF electrode is gradually activated.A fter 150 cycles, the M-NF electrode displays ad ramatically decreasing trend due to the gradual accumulationo fv olumee xpansion as ar esult of structural collapse( Figure S7 ai nt he Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Additionally,t he discharge platformso ft he NCM-NC and M-NF electrodes shift to lower voltages at high current density,w hich implies that more electrons are congested on the surfaceo ft he electrode (FigureS6b,c in the Supporting Information). [36] The specific capacity of the hollow NiÀ Co skeletons essentially remained stable during the first 200 cycles. Figure 6c displays the cycling performance of NCM-NC,M -NF,a nd NiÀCo skeleton electrodes at ac urrent density of 0.2 Ag À1 over the voltage range of 0.01-3.0 V. The M-NF electrode exhibits as lowly increasing trend during the first 155 cycles because the M-NF electrode is gradually activated.A fter 150 cycles, the M-NF electrode displays ad ramatically decreasing trend due to the gradual accumulationo fv olumee xpansion as ar esult of structural collapse( Figure S7 ai nt he Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
“…[25] By comparison with the preparation detailso fN i ÀCo PBAs in previous reports ( Table S1 in the Supporting Information), and in combination with experimental verification ( Figure S1 a-c in the Supporting Information), we concluded that the as-prepared NiÀCo PBAs with much smallerp articles izes might be assignedt ot he differencei n the concentrationo ft he solutions and masses of the reagents. [36] Owing to the nanoscale Kirkendall effect, [37] the NiÀCo PBAs changed to larger sizes and hollow structuresa fter selfassembly. [36] Owing to the nanoscale Kirkendall effect, [37] the NiÀCo PBAs changed to larger sizes and hollow structuresa fter selfassembly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations